Does early return to theatre add value to rates of revision at 3 years in assessing surgeon performance for elective hip and knee arthroplasty? A national observational study - Bottle,RA; Chase,HE; Aylin,P; Loeffler,M (BMJ Quality & Safety, 2017)
Background Joint replacement revision is the most widely used long-term outcome measure in elective hip and knee surgery. Return to theatre (RTT) has been proposed as an additional outcome measure, but how it compares with revision in its statistical performance is unknown.Methods National hospital administrative data for England were used to compare RTT at 90 days (RTT90) with revision rates within 3 years by surgeon. Standard power calculations were run for different scenarios. Funnel plots were used to count the number of surgeons with unusually high or low rates.Results From 2006 to 2011, there were 297 650 hip replacements (HRs) among 2952 surgeons and 341 226 knee replacements (KRs) among 2343 surgeons. RTT90 rates were 2.1% for HR and 1.5% for KR; 3-year revision rates were 2.1% for HR and 2.2% for KR. Statistical power to detect surgeons with poor performance on either metric was particularly low for surgeons performing 50 cases per year for the 5 years. The correlation between the risk-adjusted surgeon-level rates for the two outcomes was +0.51 for HR and +0.20 for KR, both p<0.001. There was little agreement between the measures regarding which surgeons had significantly high or low rates.Conclusion RTT90 appears to provide useful and complementary information on surgeon performance and should be considered alongside revision rates, but low case loads considerably reduce the power to detect unusual performance on either metric.